Transcriptional Analysis of Metabolic Pathways and Regulatory Mechanisms of Essential Oil Biosynthesis in the Leaves of Cinnamomum camphora (L.) Presl - Hou, Jiexi; Zhang, Jie; Zhang, Beihong; Jin, Xiaofang; Zhang, Haiyan; Jin, Zhinong (Frontiers in Genetics, 2020)
The roots, bark, and leaves of Cinnamomum camphora are rich in essential oils which are mainly comprised of monoterpenes and sesquiterpenes. Although the essential oils obtained from C. camphora have been widely used in pharmaceutical, medicinal, perfume, and food industries, the molecular mechanisms underlying terpenoid biosynthesis are poorly understood. To address this lack of knowledge, we performed transcriptome analysis to investigate the key regulatory genes involved in terpenoid biosynthesis in C. camphora. High oil yield trees of linalool-type and low oil yield trees were used to assemble a de novo transcriptome of C. camphora. A total of 121,285 unigenes were assembled and the total length, average length, N50 and GC content of unigenes were 87,869,987 bp, 724 bp, 1,063 bp, and 41.1%, respectively. Comparison of the transcriptome profiles of linalool-type C. camphora with trees of low oil yield resulted in a total of 3,689 differentially expressed unigenes. Totally 31 candidate genes had annotations associated with metabolism of terpenoids and polyketides, including four in the monoterpenoid biosynthesis pathway and three in the terpenoid backbone biosynthesis pathway. Collectively, this genome-wide transcriptome provides a valuable tool for future identification of genes related to essential oil biosynthesis. Additionally, the identification of a cohort of genes in the biosynthetic pathways of terpenoids provides a theoretical basis for metabolic engineering of essential oils in C. camphora.